Usabilidade e recomendabilidade de um site interativo visando promover mudanças comportamentais em usuários de computador - Giorgette Filho, Evandro Carlos (Universidade Federal de São Carlos, 2025)
Introduction: The growth in the use of technology has led workers to use computers for long periods of time, both at work and leisure time. Prolonged computer use is associated with a sedentary lifestyle. Sedentary behavior is a risk factor for several health problems, and changing this behavior can be promoted through technology. Objective: To test the usability of an interactive website (Habitus) with the aim of promoting behavioral changes in computer users. Methods: Health experts evaluated the content of the Habitus website blog. Computer experts were invited to perform a heuristic evaluation divided into three stages (pre-evaluation, evaluation, and session with evaluators and developers). Subsequently, computer users, graduate and undergraduate students were invited to participate in the study through social networks and by email. Participants completed an initial questionnaire containing sociodemographic data, lifestyle habits, and musculoskeletal symptoms. A link to access the Habitus application was made available so that participants could use the website. After one month, a feedback and recommendation questionnaire was sent regarding the usability of the website. Results: Eight health experts reviewed the content of the Habitus blog. Three evaluators performed a heuristic evaluation of the Habitus website and changes were made. Forty computer users evaluated the website for one month. The usability score obtained was 86.94 and users indicated a 35% chance of recommending the website to colleagues. Conclusion: the Habitus website has excellent usability and is well received by users, but there is potential for improvements to increase customer satisfaction and usage.
Usability and recommendability of an interactive website aimed at promoting behavioral changes in computer users
Keywords: Fisioterapia; Ergonomia; Saúde do trabalhador; Inatividade física; Saúde do trabalhador; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar